1997
DOI: 10.1007/s004310050750
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acid deficiency in well nourished young cystic fibrosis patients

Abstract: Essential fatty acid deficiency is present in young cystic fibrosis subjects in the absence of protein-energy malnutrition. It means that this deficiency is probably related to specific defects in fatty acid metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
99
2
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 37 publications
9
99
2
5
Order By: Relevance
“…The other consistent fatty acid alteration (decreased DHA levels) was described in the blood and tissues of CF patients (11)(12)(13)(14). Other reported fatty acid abnormalities in CF include increased palmitoleic acid (16:1n-7) and eicosatrienoic acid (20:3n-9) in the plasma of CF patients (6,13,15,16). In addition to these fatty acid alterations, increased arachidonic acid (AA) release from CF lymphocytes and from epithelial cell lines carrying the DF508 CFTR mutation has been described (17,18).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The other consistent fatty acid alteration (decreased DHA levels) was described in the blood and tissues of CF patients (11)(12)(13)(14). Other reported fatty acid abnormalities in CF include increased palmitoleic acid (16:1n-7) and eicosatrienoic acid (20:3n-9) in the plasma of CF patients (6,13,15,16). In addition to these fatty acid alterations, increased arachidonic acid (AA) release from CF lymphocytes and from epithelial cell lines carrying the DF508 CFTR mutation has been described (17,18).…”
mentioning
confidence: 64%
“…Increased LA metabolism through the n-6 pathway was described in CF pancreatic epithelial cells expressing the DF508 CFTR and in cultures of pancreatic acini from cftr 2/2 mice (9, 10). The other consistent fatty acid alteration (decreased DHA levels) was described in the blood and tissues of CF patients (11)(12)(13)(14). Other reported fatty acid abnormalities in CF include increased palmitoleic acid (16:1n-7) and eicosatrienoic acid (20:3n-9) in the plasma of CF patients (6,13,15,16).…”
mentioning
confidence: 71%
“…These alterations include a decrease in circulating essential fatty acids ( 19,20 ), phospholipids, and lysophospholipids ( 21 ); decreased polyunsaturated fatty acids in lung, intestine, and pancreas of mice ( 22,23 ) and nasal cells of patients ( 24 ), mostly associated with an imbalanced n-3/n-6 ratio; and decreased linoleic acid ( 19,25 ) and lipoxin A4 in lung exudates from patients ( 26 ). These alterations have been attributed largely to malabsorption ( 19 ), increased fl ux through the n-6 biosynthetic pathway ( 25,27,28 ), and an alteration in the methionine-homocysteine cycle ( 29,30 ).…”
Section: Lc-msmentioning
confidence: 99%
“…Current high-fat, hypercaloric nutritional strategies and improved pancreas enzyme replacement therapies can usually maintain patients in optimal nutritional status, thus normalizing EFA status in many CF patients (5). Nonetheless, several reports still indicate the occurrence of EFA deficiency in CF (6)(7)(8). Although some authors have suggested that residual fat malabsorption and increased EFA turnover in CF may compromise EFA status (9,10), the exact pathophysiology of EFA deficiency in CF patients has not been elucidated.…”
mentioning
confidence: 99%